2020
DOI: 10.1111/os.12789
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostic Value of MRI Lamellated Hyperintense Synovitis in Periprosthetic Infection of Hip

Abstract: Objective: To investigate the correlation between magnetic resonance imaging (MRI) lamellated hyperintense synovitis and periprosthetic infection of hip arthroplasty and estimate its value in the diagnosis of infection after hip replacement. Methods: A retrospective analysis of 50 patients who underwent MRI from January 2016 to June 2019 after hip replacement was performed. The MRI scanning was performed with a 1.5T clinical imaging unit using SEMAC protocols. A total of 25 patients (cohort 1) showed infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…Some papers reported high sensitivity and specificity of lamellated hyperintense synovitis as an MRI characteristic of PJI in patients with knee [87,88] and hip [89] prosthesis. Lamellated hyperintense synovitis in an MRI image refers to the thickened synovial tissue nearby the joint in MRI, and "high signal" refers to the high signal in the T2WI sequence image.…”
Section: Prosthetic Infectionsmentioning
confidence: 99%
“…Some papers reported high sensitivity and specificity of lamellated hyperintense synovitis as an MRI characteristic of PJI in patients with knee [87,88] and hip [89] prosthesis. Lamellated hyperintense synovitis in an MRI image refers to the thickened synovial tissue nearby the joint in MRI, and "high signal" refers to the high signal in the T2WI sequence image.…”
Section: Prosthetic Infectionsmentioning
confidence: 99%
“…However, in this study, the sole predictive value of MRI findings was not investigated. Gao et al found that the sensitivity of lamellated hyperintense synovitis for infection was 0.80 to 0.88 and the specificity was 0.84 to 0.92 [ 33 ]. Another study showed that the sensitivity of lamellated hyperintense synovitis for infection was 0.86 to 0.92 and the specificity was 0.85 to 0.87, with almost perfect interobserver agreement and intraobserver agreement [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the AUC of CRP levels was 0.9 [ 37 ]. Gao found that the sensitivity and specificity of MRI in the prediction of infection were only 0.80 and 0.84, respectively [ 33 ]. In the present study, the AUC of this new scoring system was 0.965, which was the highest among the scoring systems and demonstrated the strength of this comprehensive predictive system.…”
Section: Discussionmentioning
confidence: 99%
“…Since the development of advanced metal artifact reducing techniques, magnetic resonance imaging scans provided an optimal sensitivity and specificity for the diagnosis of PJI after hip arthroplasty with improved diagnostic value. [ 27 ] Also, nuclear scan such as leukocyte–bone marrow scintigraphy or fluorodeoxyglucose PET have been shown to be sensitive for diagnosis of PJI. [ 28 ] However, imaging modality is currently not part of the musculoskeletal infection society criteria for diagnosing PJI.…”
Section: Discussionmentioning
confidence: 99%